Vertical overlap of probability density functions of cloud and precipitation hydrometeors. Issue 21 (5th November 2016) - Ovchinnikov, Mikhail; Lim, Kyo‐Sun Sunny; Larson, Vincent E.; Wong, May; Thayer‐Calder, Katherine; Ghan, Steven J.
Abstract: Coarse‐resolution climate models increasingly rely on probability density functions (PDFs) to represent subgrid‐scale variability of prognostic variables. While PDFs characterize the horizontal variability, a separate treatment is needed to account for the vertical structure of clouds and precipitation. When subcolumns are drawn from these PDFs for microphysics or radiation parameterizations, appropriate vertical correlations must be enforced via PDF overlap specifications. This study evaluates the representation of PDF overlap in the Subgrid Importance Latin Hypercube Sampler (SILHS) employed in the assumed PDF turbulence and cloud scheme called the Cloud Layers Unified by Binormals (CLUBB). PDF overlap in CLUBB‐SILHS simulations of continental and tropical oceanic deep convection is compared with overlap of PDF of various microphysics variables in cloud‐resolving model (CRM) simulations of the same cases that explicitly predict the 3‐D structure of cloud and precipitation fields. CRM results show that PDF overlap varies significantly between different hydrometeor types, as well as between PDFs of mass and number mixing ratios for each species—a distinction that the current SILHS implementation does not make. In CRM simulations that explicitly resolve cloud and precipitation structures, faster falling species, such as rain and graupel, exhibit significantly higher coherence in their vertical distributions than slow falling cloud liquid and ice. These results suggest that to improve the overlap treatment in the subcolumn generator, the PDF correlations need to depend on hydrometeor properties, such as fall speeds, in addition to the currently implemented dependency on the turbulent convective length scale. Key Points: Vertical correlations between microphysics variables are studied in CLUBB SILHS and CRM Rank correlations vary greatly between various hydrometeor types in CRM‐predicted fields PDFs of faster falling hydrometeors exhibit greater vertical coherence